Experimental Comparison of Double-Stage Runner Profiles in Gravitational Water Vortex Turbines for Improved Performance - Risdiyanto, Gunawan; Septiyanto, Muhamad Dwi; Hadi, Syamsul; Tjahjana, Dominicus Danardono Dwi Prija; Budiana, Eko Prasetya; Andriyanto, Solikin (Rekayasa, 2025)
Gravity Water Vortex Turbines (GWVTs) are a new category of turbines used in micro-hydro power plants (MHPs). GWVTs can be used to optimize existing water flow potential, aerate water bodies, and maintain ecosystem integrity. The basic idea for this development stems from previous research showing that GWVTs with conical basins exhibit different flow velocity distributions at different locations. To exploit this potential, experimental analysis was conducted using a two-stage configuration with varying runner profiles and different flow rate conditions. A low-speed water tunnel with a conical basin was used to generate the vortex flow. Furthermore, the performance of the double-stage GWVT was compared with that of a single-runner GWVT in terms of power conversion. The study used several turbine configurations profiles, including Savonius and Flat with Curved. The findings measured torque, mechanical power conversion, and rotational speed. The GWVT performance results were evaluated using comparison-staging and inter-staging methods to determine the best performance of each turbine in generating power. The results showed that the Savonius blade profile on a single-runner GWVT installed in the lower stage position was superior in terms of power conversion. The best power generated is 53.7 Watts, and the efficiency is 52.3% at a flow rate of 9.1 L/s. The installation of two similar runners on a double-stage GWVT yields better power conversion than the installation of two different runners. A flat with Curved runners installed for the lower and upper stages on a double-stage GWVT shows the highest results of 56.7 Watts and 1.2 Watts. So, it can be concluded that the power conversion of a double-stage GWVT is superior to that of a single-runner GWVT.